2002
DOI: 10.1039/b205254g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization of an AlPO-CJ2analogue containing heteroatomic Eu

Abstract: An analogue of AlPO-CJ2 microporous aluminophosphate containing heteroatomic Eu was hydrothermally synthesized in situ in the reactant system of carbamide-NH4-F-Al2O3-P2O5-H2O, and characterization by ICP, powder XRD, Mössbauer spectra, 31P MAS NMR and luminescent spectroscopy prove that Eu is incorporated into the framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…According to the previous reports, the replacement of Al 3+ in zeolite framework by Eu 3+ can cause the shift of 31 P MASNMR peak. [29] Furthermore, ICP results give that the Al/P ratios of pure AlPO 4 -5 zeolite and (Al+Eu)/P ratio of CDs@EuAPO-5 composite are nearly, 0.96 and 0.97, respectively, which further confirms the replacement of Al 3+ of zeolite framework by Eu 3+ . [29] It is worth mentioning that the CDs@EuAPO-5 composite only displays a low total quantum yield (QY) of 5%, which is because we decrease the crystallization temperature to achieve the meanwhile strong emissions of CDs and Eu 3+ .…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…According to the previous reports, the replacement of Al 3+ in zeolite framework by Eu 3+ can cause the shift of 31 P MASNMR peak. [29] Furthermore, ICP results give that the Al/P ratios of pure AlPO 4 -5 zeolite and (Al+Eu)/P ratio of CDs@EuAPO-5 composite are nearly, 0.96 and 0.97, respectively, which further confirms the replacement of Al 3+ of zeolite framework by Eu 3+ . [29] It is worth mentioning that the CDs@EuAPO-5 composite only displays a low total quantum yield (QY) of 5%, which is because we decrease the crystallization temperature to achieve the meanwhile strong emissions of CDs and Eu 3+ .…”
Section: Resultsmentioning
confidence: 62%
“…[29] Furthermore, ICP results give that the Al/P ratios of pure AlPO 4 -5 zeolite and (Al+Eu)/P ratio of CDs@EuAPO-5 composite are nearly, 0.96 and 0.97, respectively, which further confirms the replacement of Al 3+ of zeolite framework by Eu 3+ . [29] It is worth mentioning that the CDs@EuAPO-5 composite only displays a low total quantum yield (QY) of 5%, which is because we decrease the crystallization temperature to achieve the meanwhile strong emissions of CDs and Eu 3+ . If we increase the crystallization temperature, the fluorescence emission of CDs will further strengthen, and the QY should be greatly improved, [41] but the fluorescence emission of Eu 3+ will weaken (Figure S10, Supporting Information), making it difficult to realize triple emissions in a single composite.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…: +86 0312 5079423; fax: +86 0312 5011174. AlPO 4 -CJ 2 [12]. Yan et al reported the substitution of rare earth (RE) elements (Eu, Ce, Tb) on the large-pore aluminophosphate and mesoporous aluminophosphate [13].…”
Section: Introductionmentioning
confidence: 98%